A Data-Centric Study of Software Tutorial Design - Arya, Deeksha M.; Nassif, Mathieu; Robillard, Martin P. (IEEE software, 2022)
We investigate three tutorials on Android development to elicit design choices related to their organization and content. We describe decision points and tradeoffs and propose guidelines to assist tutorial authors in making explicit and informed decisions about the design of tutorials